Development and Validation of a Disease-Specific Questionnaire for Basal Joint Arthritis - Noback, Peter C.; Lombardi, Joseph M.; Seetharaman, Mani; Lee, Donald H.; Strauch, Robert J.; Rosenwasser, Melvin P. (Journal of Wrist Surgery, 2017)
Background The Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire is the most commonly used instrument to assess outcomes of basal joint arthritis (BJA). However, the DASH is subject to influence by the entire upper extremity.Purpose This study aims to develop and validate a disease-specific questionnaire for BJA that would be more sensitive to changes in thumb function and pain, and correlate better with objective and subjective metrics.Patients and Methods The thumb disability examination (TDX) was developed and 80 patients presenting with BJA at one of the two hospital-based hand clinics were enrolled in the validation study. At enrollment, subjects were given the TDX, DASH, and visual analog pain scale with activity (A-VAS) surveys. The strength was assessed. Patients receiving corticosteroid injection were seen for follow-up at 6 weeks and those who underwent surgery were seen between 3 and 6 months postoperatively. Both the groups were given the TDX, DASH, and A-VAS scales at follow-up.Results In total, 65 subjects were included in the analysis. Average TDX completion time was 134.3 seconds. The TDX correlated more strongly with A-VAS scores at baseline than the DASH, but less strongly with tip-pinch measures. The TDX was more responsive to injection and surgical treatments for BJA than the DASH, yielding a larger effect size and standardized response mean, and was the only instrument to significantly correlate with changes in A-VAS.Conclusion The TDX is a reliable instrument for assessing BJA treatment outcomes. It bears less of a burden on patients, is more responsive to symptomatic changes, and correlates better with most objective and subjective measures than the DASH.Level of Evidence II, diagnostic.
Keywords: thumb carpometacarpal arthritis; basal joint; outcome instrument; thumb disability examination; disease specific